2009
DOI: 10.1213/ane.0b013e3181966f03
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Obturator Nerve Block: A Sonoanatomic Study of a New Methodologic Approach

Abstract: Landmarks defined in this clinical trial can be used in patients for obturator nerve block with ultrasound guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 12 publications
1
40
1
3
Order By: Relevance
“…They reported patient satisfaction rates as high as 93%. 26 These rates show that ultrasound-guided ONB is more successful than a nerve stimulator technique.…”
Section: Discussionmentioning
confidence: 97%
“…They reported patient satisfaction rates as high as 93%. 26 These rates show that ultrasound-guided ONB is more successful than a nerve stimulator technique.…”
Section: Discussionmentioning
confidence: 97%
“…The study by Thallaj and colleagues (9) revealed that ultrasound-guided blockage of obturator nerve was successful in preventing an adductor spasm in all except one patient and patient and surgeon's satisfaction were adequate. In a single-group study among 15 subjects under ultrasound-guided blockage of obturator nerves by Akkaya et al (10) in Turkey, it was demonstrated that ninety-three percent of the patients reported satisfaction from the block.…”
Section: Discussionmentioning
confidence: 98%
“…[13,14] Bu konvansiyonel yaklaşımların dışında US'nin rejyonal anestezi pratiği-ne girmesiyle birlikte OSB'nin de US eşliğinde yapıldığı teknikler de tanımlanmıştır. [15][16][17] Wassef [13] 1993 yılın-da anatomik noktalara dayanan interadduktor tekniği tanımlamıştır. Biz kliniğimizde bu teknikle Wassef'in anatomik noktalara dayanan interadduktor yaklaşımı-nı US eşliğinde in-plane teknikle uygulamaktayız.…”
Section: Discussionunclassified